Innovation capability in medical sciences universities: A qualitative study of Iran - Fatemeh Ghardashi; Maryam Yaghoubi; Mohammadkarim Bahadori; Ehsan Teymourzadeh (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Innovation is a competitive advantage, with its preservation and continuity dependent on the organizational innovation capability. This study was conducted with the aim of determining the innovation capability dimensions and components in medical sciences universities of Iran. METHODS: The present study is a qualitative study with content analysis approach, undertaken in 2016-2017. The data processing included 10 deep interviews with the experts of the health innovation domain in top management of the three types of the medicine sciences universities of Iran with >5 years of experience. Targeted data sampling was performed using snowball method and continued until the saturation of the data. Data analysis was performed using conventional content analysis method using Maxqda 12 software. RESULTS: Data analysis resulted in the extraction of 28 categories and 8 main themes including communications and interactions, innovation climate, university setting, policy factors (policy-making, rules and regulations), organizational culture, organizational resources, management and leadership, and organizational learning in two university internal and external dimensions. CONCLUSION: To accelerate innovation in medical sciences universities, recognizing the potential of innovation capability is essential.